Analisis Promosi Penjualan Dan Kemudahan Terhadap Keputusan Penggunaan Shopeepay (Survei Pada Mahasiswa Universitas Muhammadiyah Sukabumi) - Mochamad Iqbal Zulfikar; Kokom Komariah; Acep Samsudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The development of technology in Indonesia in the era of globalization is very rapid, one of which is progress in the economic field, namely in payment transactions using e-money. The development of e-money is directly proportional to the increase in public purchases through the marketplace. Shopee as one of the marketplaces provides e-money shopeepay as a payment method. Promotion and ease of use are important factors for consumers in deciding which payment method to use. The results showed that there was a positive influence of sales promotion on the decision to use shopeepay as evidenced by the t-count value of 4.095 and the regression coefficient of 0.326. Ease of use also has a positive effect on the decision to use shopeepay as evidenced by the t-count value of 8.339 and the regression coefficient of 0.832. From the results of simultaneous testing using the F test, it shows that sales promotion and ease of use have a positive effect on the decision to use shopeepay with a calculated F value of 83,319.